Pengaruh Brand Image dan Store Atmosphere terhadap Keputusan Konsumen Pada Cortans Koffie - Rifky Panandra; Rizqon Jamil Farhas; Efti Novita Sari (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The aim of this study is to investigate how the environment and brand image of Cortans Koffie affect the decisions made by its clients. One hundred respondents who were chosen using non-probability sampling approaches were given questionnaires as part of the descriptive quantitative research methodology. SPSS version 26 was used to analyze the data. With a significance value of 0.000 <0.05, the study's findings show that brand image significantly and favorably affects consumer choices. The impact of shop atmosphere is likewise significant (0.001 <0.05). The R2 value of 0.408 shows that brand image and store environment influence 40.8% of consumer decisions at Cortans Koffie, while the R value of 0.639 shows a strong association with customer decisions, with other factors influencing the remaining percentage. According to the study's findings, store environment and brand image have a significant impact on customer choices, particularly among the younger generation, who makes up the majority of the coffee shop market (Cortans Koffie). In order to make customers feel at home and encourage repeat business, business owners should continue to uphold and enhance their brand image by offering consistently high-quality products and amiable service. They should also strengthen the store atmosphere by adding more beautiful interior design, cozy lighting, and a welcoming environment.